Influence of pipe bedding on their structural integrity - Kuliczkowski, Andrzej; Kuliczkowska, Emilia (Instal, 2023)
The method of calculating the load capacity of pipes recommended in the ATV guidelines is given. It is approximate. Then, the proposed exact method of calculations is given. The recommendations for determining the bedding coefficient, which have a very significant impact on the load capacity of pipes after their installation, have been reviewed. There are three examples of different pipe beddings indicating the consequences of more unfavorable and more favorable pipe beddings in relation to the recommended beddings.